S-layer proteins in microencapsulated freeze-dried probiotic Levilactobacillus brevis strains - Nina Čuljak; Andreja Leboš Pavunc; Kristina Dučkić; Katarina Butorac; Martina Banić; Jasna Novak; Jagoda Šušković; Blaženka Kos (Mljekarstvo)
The presence of surface (S)-layer proteins as a rare property of lactic acid bacteria plays an important role in the expression of the probiotic properties of the producer strain and protects the cells from unfavourable environmental conditions. Therefore, the aim of this work was to evaluate the role of S-layer proteins of four Levilactobacillus brevis MB1, MB2, MB13, and MB20 strains, previously isolated from human milk. The results showed better survival under simulated gastrointestinal tract (GIT) conditions and better adhesion to Caco-2 cells, achieved when S-proteins were present on the surface of the examined probiotic Levilactobacillus brevis strains. Free cells and cells microencapsulated in alginate, with or without galactooligosaccharides (GOS) and fructooligosaccharides (FOS), survived in high numbers during freeze-drying and one-month storage at 4 °C, as well as during exposure to simulated GIT conditions (>108 CFU/g), thus fulfilling the primary technological criterion for the selection of probiotic strains. Higher survival of freeze-drying of encapsulated cells than free cells, can be attributed to the protective effect of alginate, GOS and FOS as prebiotic agents. However, GOS was more protective than FOS in maintaining the viability of microencapsulated Levilactobacillus brevis MB1, MB2, MB13 and MB20 cells in alginate during storage and under the harsh conditions of GIT and freeze-drying.